1981
DOI: 10.1084/jem.153.3.569
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of human large granular lymphocytes and relationship to natural killer and K cells

Abstract: Recent evidence, has demonstrated an association between a subpopulation of peripheral blood mononuclear cells, morphologically identified as large granular lymphocytes (LGL), and natural killer (NK) activity. We have now evaluated more directly the role of LGL in both NK activity and antibody- dependent cellular cytotoxicity (ADCC), by using highly enriched populations of LGL, obtained by centrifugation of peripheral blood mononuclear cells on Percoll discontinuous density gradients. Both spontaneous and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
233
1
2

Year Published

1983
1983
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 916 publications
(251 citation statements)
references
References 31 publications
13
233
1
2
Order By: Relevance
“…The nonadherent PBMC was fractionated by a seven-step Percoll gradient as previously described (18), and the enriched monocyte populations (containing 65-85% of CD14 ϩ cells) were obtained at the very top of the gradient (top fraction). The cells were collected and washed twice with ice-cold PBS.…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…The nonadherent PBMC was fractionated by a seven-step Percoll gradient as previously described (18), and the enriched monocyte populations (containing 65-85% of CD14 ϩ cells) were obtained at the very top of the gradient (top fraction). The cells were collected and washed twice with ice-cold PBS.…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…Large granular lymphocytes (LGL) account for approximately 10% of peripheral blood mononuclear cells in human [1]. Immunophenotypically, LGLs can be natural killer cells (CD3 À ) or T cells (CD3 + ).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that a minor proportion of blood and tumour-associated NK cells kill autologous tumour cells freshly isolated from the same cancer patients (Uchida & Micksche, 1983a). Recent reports have indicated that human NK cells activity is strongly associated with a morphological subpopulation of lymphoid cells, termed large granular lymphocytes (LGL) (Timonen et al, 1981). Although LGL are not synonymous with NK cells, more than 50% of…”
mentioning
confidence: 99%